Simvastatin and atorvastatin attenuate VCAM-1 and uPAR expression on human endothelial cells and platelet surface expression of CD40 ligand - Stach-Jablonski, Ksenija; Nguyen, Xuan-Duc; Lang, Siegfried; Elmas, Elif; Weiß, Christel; Borggrefe, Martin; Fischer, Joachim E.; Kälsch, Thorsten (Cardiology journal, 2012)
Background: In addition to their cholesterol lowering ability, statins have proven pleiotropic effects in the cardiovascular system. Chronic inflammation with interactions between platelets and endothelial cells leads to an upregulation of activity markers of atherosclerosis. The purpose of this study was to investigate the effects of simvastatin and atorvastatin on platelets and endothelial cells in an in vitro endothelial cell model. Methods and Results: After a 24 h incubation period with either simvastatin or atorvastatin (1 μmol/L), human umbilical vein endothelial cells were stimulated for 1 h with lipopolysaccharide (LPS), and were then incubated in direct contact with activated platelets. Platelet surface expression of CD40L and CD62P and expression of ICAM-1, VCAM-1, uPAR and MT1-MMP on endothelial cells were measured by flow cytometry. Supernatants were analyzed by ELISA for soluble MMP-1. The increased expression of VCAM-1 and uPAR on endothelial cells by stimulation with LPS and by direct contact with activated platelets was significantly reduced to a similar extent through pre-incubation with both atorvastatin and simvastatin (p < 0.005). Conclusions: These effects may explain the ability of statins to reduce the progression of atherosclerosis in addition to their cholesterol-lowering properties.
Gesehen am 09.08.2018